2011
DOI: 10.1039/c0em00535e
|View full text |Cite
|
Sign up to set email alerts
|

Saharan dust contribution to PM10, PM2.5 and PM1 in urban and suburban areas of Rome: a comparison between single-particle SEM-EDS analysis and whole-sample PIXE analysis

Abstract: , a period characterised by two episodes of Saharan dust outbreaks in Italy, particulate matter (PM) samples were collected at two stations (urban and suburban) in Rome. Some samples were selected and analysed using the SEM-EDS technique to characterise PM, focussing especially on the mineral contribution. Samples were representative both of days affected by Saharan dust episodes and days without this contribution. Cluster analysis allowed the attribution of each of about 67 000 analysed particles to one of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 43 publications
1
38
0
1
Order By: Relevance
“…Al / Si ratios > 0.3 are generally considered indicators of desert dust (Molinaroli, 1996;Guerzoni et al, 1997;Blanco et al, 2003;Kandler et al, 2007;Matassoni et al, 2011), however Coude-Gaussen et al (1987) have already found that the Al / Si ratio can vary with particle size. They noted that finest fractions have an Al / Si ratio significantly lower than that of mean aerosols, with values below 0.3, due to larger amounts of quartz.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Al / Si ratios > 0.3 are generally considered indicators of desert dust (Molinaroli, 1996;Guerzoni et al, 1997;Blanco et al, 2003;Kandler et al, 2007;Matassoni et al, 2011), however Coude-Gaussen et al (1987) have already found that the Al / Si ratio can vary with particle size. They noted that finest fractions have an Al / Si ratio significantly lower than that of mean aerosols, with values below 0.3, due to larger amounts of quartz.…”
Section: Discussionmentioning
confidence: 99%
“…Laskin et al, 2002). Furthermore, the behavior of the hygroscopic NaCl particles can encourage aggregation with silicate particles, abundant in Saharan dust outbreaks (Levin et al, 2005;Matassoni et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that all the sites experienced a certain marine influence. In the PM 10 samples, Ca (Choi et al, 2001;Arimoto et al, 2004;Cao et al, 2005b;Shen et al, 2007;Matassoni et al, 2011;Galindo et al, 2013). This calls, in first hypothesis, for the possibility of these particulate matter to mainly originate from Sahara dust.…”
Section: Chemical Composition Of Pm 10 and Pm 25mentioning
confidence: 99%
“…[3][4][5] In addition, in the nature, SiNPs mainly exist in soil, sand, ore, and particulate matter. 6,7 Due to increasing atmospheric pollution, enhanced concentrations of SiNPs are found in the environment. 2,8 There is a concern that research on the possible health risks of SiNPs are not keeping pace with the rapid growth in the number of SiNP products.…”
Section: Introductionmentioning
confidence: 99%